Pendampingan Dan Pembuatan Video Profil Sebagai Pengabdian Kepada Masyarakat Desa Wisata Sama Guna Kabupaten Lombok Utara - Rusyada, Gozin Najah; Hidayat, Irfan; Gunalan, Sasih (CV. Global Cendekia Inti, 2024)
Sama Guna tourist village in North Lombok Regency has great natural and cultural tourism potential. However, limitations in promotion are a major challenge for the village to attract more tourists. One solution that can be done is to make an informative and interesting village profile video. This community service activity is in the form of mentoring and making a video profile of Sama Guna Tourism Village. This activity actively involves the local community to explore the potential of the village, build promotional narratives, and produce profile videos that authentically represent the village identity. The service method adopts the Participatory Action Research (PAR) service model, with stages including preparation, implementation, and evaluation. The results of the activity show an increase in community understanding of the importance of digital promotional media, as well as producing profile videos that are ready to be used to promote tourist villages on various platforms.